2014
DOI: 10.1055/s-0034-1377930
|View full text |Cite
|
Sign up to set email alerts
|

Competence development in ERCP: the learning curve of novice trainees

Abstract: Learning curves are a valuable means for assessing competence in ERCP. Differences in learning curves can be shown with RAF-E. Verification of competence should be based on actual performance, instead of minimum numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 15 publications
2
100
1
Order By: Relevance
“…The Rotterdam Assessment Form for ERCP (RAF-E) has been shown to be a good tool to allow determination of the progress of every individual trainee with respect to different aspects of ERCP 1. The RAF-E records cannulation rates and other interventions such as stent removal or insertion.…”
Section: Training Methods For Ercp and Eusmentioning
confidence: 99%
See 2 more Smart Citations
“…The Rotterdam Assessment Form for ERCP (RAF-E) has been shown to be a good tool to allow determination of the progress of every individual trainee with respect to different aspects of ERCP 1. The RAF-E records cannulation rates and other interventions such as stent removal or insertion.…”
Section: Training Methods For Ercp and Eusmentioning
confidence: 99%
“…The RAF-E records cannulation rates and other interventions such as stent removal or insertion. Historically, competence was merely based on ERCP numbers, but as van Ekkelenkamp et al and other studies show achieving a predefined action (eg, cannulation) is more important than procedure numbers per se 1 2 32 33. But when it comes to numbers, the Ekkelenkamp study showed successful common bile duct (CBD) cannulation in a virgin papilla of only 68% after 180 ERCPs.…”
Section: Training Methods For Ercp and Eusmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research supports establishing a standard of 80-90% technical success before trainees are deemed competent in a specific skill [9]. Nevertheless, individual trainees may differ in the acquisition of technical skills.…”
Section: Endoscopic Retrograde Cholangiopancreatographymentioning
confidence: 95%
“…Recently, a study reported the use of a standardized form for continuous self-assessment. The form included previously proposed quality indicators for ERCP such as procedural indication, degree of technical difficulty, previous ERCP failure, and success or failure options (such as cannulation of the common bile duct [CBD] or pancreatic duct, stent placement, sphincterotomy, and stone extraction) [9]. This method allowed not only for the quantitative evaluation of trainees, but also determined the learning curve of each individual and of the average group progression.…”
Section: Endoscopic Retrograde Cholangiopancreatographymentioning
confidence: 99%